Electronic Excited States of Tungsten(0) Arylisocyanides - Kvapilová, Hana; Sattler, Wesley; Sattler, Aaron; Sazanovich, Igor V; Clark, Ian P; Towrie, Michael; Gray, Harry B; Záliš, Stanislav; Vlček, Antonín (Inorganic chemistry, 2015)
W(CNAryl)6 complexes containing 2,6-diisopropylphenyl isocyanide (CNdipp) are powerful photoreductants with strongly emissive long-lived excited states. These properties are enhanced upon appending another aryl ring, e.g., W(CNdippPh(OMe2))6; CNdippPh(OMe2) = 4-(3,5-dimethoxyphenyl)-2,6-diisopropylphenylisocyanide (Sattler et al. J. Am. Chem. Soc. 2015, 137, 1198-1205). Electronic transitions and low-lying excited states of these complexes were investigated by time-dependent density functional theory (TDDFT); the lowest triplet state was characterized by time-resolved infrared spectroscopy (TRIR) supported by density functional theory (DFT). The intense absorption band of W(CNdipp)6 at 460 nm and that of W(CNdippPh(OMe2))6 at 500 nm originate from transitions of mixed ππ*(C≡N-C)/MLCT(W → Aryl) character, whereby W is depopulated by ca. 0.4 e(-) and the electron-density changes are predominantly localized along two equatorial molecular axes. The red shift and intensity rise on going from W(CNdipp)6 to W(CNdippPh(OMe2))6 are attributable to more extensive delocalization of the MLCT component. The complexes also exhibit absorptions in the 300-320 nm region, owing to W → C≡N MLCT transitions. Electronic absorptions in the spectrum of W(CNXy)6 (Xy = 2,6-dimethylphenyl), a complex with orthogonal aryl orientation, have similar characteristics, although shifted to higher energies. The relaxed lowest W(CNAryl)6 triplet state combines ππ* excitation of a trans pair of C≡N-C moieties with MLCT (0.21 e(-)) and ligand-to-ligand charge transfer (LLCT, 0.24-0.27 e(-)) from the other four CNAryl ligands to the axial aryl and, less, to C≡N groups; the spin density is localized along a single Aryl-N≡C-W-C≡N-Aryl axis. Delocalization of excited electron density on outer aryl rings in W(CNdippPh(OMe2))6 likely promotes photoinduced electron-transfer reactions to acceptor molecules. TRIR spectra show an intense broad bleach due to ν(C≡N), a prominent transient upshifted by 60-65 cm(-1), and a weak down-shifted feature due to antisymmetric C≡N stretch along the axis of high spin density. The TRIR spectral pattern remains unchanged on the femtosecond-nanosecond time scale, indicating that intersystem crossing and electron-density localization are ultrafast (<100 fs).